Risk, Age and Pregnancy - Heyman, B. author. aut Link
X, 242 p.
Keywords: Risk, Age and Pregnancy provides an in-depth case study of the operation of a prenatal genetic screening and testing system. The methodology integrates observational, qualitative interview and survey data. The perspectives of pregnant women, hospital doctors and midwives are explored in depth, as is the communication between women and the hospital doctors who advise them. The book offers insights which are relevant to those concerned with the rapidly growing field of genetic risk management.